Exploring Associations between Communication, Patient-level Factors, and Adjuvant Chemotherapy: Presenter(s): Kerri-Anne Mitchell, Austin College, United States. (April 2023) - Boyle, Joseph; Brown, Richard
Abstract : Background: Between 2016 and 2020, almost 2 million Americans were diagnosed with breast or colon cancer; almost half a million of these diagnoses resulted in death. Adjuvant chemotherapy (AC) significantly improves survival and recurrence rates in these patients, however past studies indicate wide variation in primary non-adherence (no AC) rates in breast cancer patients (10 – 83.7%), and high rates of primary non-adherence in colon cancer patients (36 – 38%). We examined the relationship between patient-level factors (demographics, disease and treatment factors, and patient experience), patient-centered communication (PCCM), and non-adherence to AC guidelines at two levels, primary non-adherence and non-persistence at three months (less than three months of AC) in elderly breast and colon cancer patients to better understand the role of PCCM in AC non-adherence. Methods: Descriptive statistics for patient-level factors, PCCM, primary non-adherence, and non-persistence at three months were obtained. Multiple logistic regression models estimated AC non-adherence after accounting for patient-level factors and PCCM. Findings: The sample (n = 577) was mostly white (87%), female (94%), diagnosed with breast cancer (87%) and reported PCCM: provider communication score ≥ 90% (73%) and provider communication score = 100% (58%). Both levels of AC nonadherence were higher in breast cancer patients (69% and 81%), respectively than colon cancer patients (43% and 45%), respectively. Male sex, survey assistance, and low/average ratings of a personal doctor, specialist, and healthcare were associated with lower PCCM. Older age, breast cancer diagnosis, and diagnosis group following 2007-2009 increased the likelihood of both levels of AC non-adherence. Comorbidities and PCCM-90 were exclusively associated with non-persistence at three months. Discussion: PCCM's relationship to AC non-adherence varied by level of PCCM, time period, and the presence of comorbidities. Simultaneous and routine evaluation of PCCM, the receipt of value-concordant care, and identified covariates may further our understanding of these interrelationships.